POLYPLACOPHORA FROM THE MIOCENE OF NORTH ITALY. PART 2: CALLOCHITONIDAE, CHITONIDAE, LEPIDOCHITONIDAE, ACANTHOCHITONIDAE AND CRYPTOPLACIDAE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
This study completes the description of the chiton fauna (Mollusca, Polyplacophora) from deposits of the Miocene marine sequence of North Italy, located in Piedmont and Emilia Romagna regions. This second and final part describes chitons belonging to five families: Callochitonidae, Chitonidae, Lepidochitonidae, Acanthochitonidae and Cryptoplacidae. Nineteen species were identified, of which two are described as new (Chiton sulcomarginatus sp. n. and Craspedochiton brunettii sp. n.), and 17 were already known. Craspedochiton mutinocrassus is the new name attributed to the species previously known as Acanthochiton costatus or A. costatus var. mutinocrassa; Chiton sulcomarginatus sp. n., Lepidochitona monterosatoi, L. pliocinerea, and Acanthochitona oblonga, previously known only up to Pliocene, are reported for the first time from the Miocene of Italy. The stratigraphic distribution of numerous species thought to first appear in the Late Miocene (Callochiton doriae, Chiton olivaceus, C. corallinus, Acanthochitona fascicularis, A. crinita, and Craspedochiton altavillensis) is here extended to the Early Miocene. The distribution of Cryptoplax weinlandi is extended to the Middle Miocene (Serravallian). In total 35 chiton species (with 3.003 valves) were identified in the Italian Miocene (including both parts of this series). Ten species became extinct at the end of the Miocene, six in the Pliocene, two in the Pleistocene, and 17 are extant. Of the extant species nine occur both in the Atlantic and Mediterranean, two exclusively in the Atlantic and six only in the Mediterranean. The number of species reported from the Torino Hill assemblages (Burdigalian?) is increased from three listed by Sacco (1897) to nine. Thirty-four of the 35 species (excluding only Lepidopleurus benoisti) occur in the Tortonian-Messinian Po Basin. Thirteen (37%) of the species are also found in the Miocene Paratethys (Austria, Poland, Czech Republic, Hungary, Romania and Ukraine), which can be explained by connections between the Proto-Mediterranean and Paratethys during the Miocene.